Pancasila Seagai Sumber Hukum Tata Negara : Implikasi Terhadap Pembentukan Undang – Undang di Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Musain Nasoha; Diva Senja Andini; Dwi Safa`atun; Aditya Putra Pratama; Rozaky Arfiantama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
As the ideological and philosophical basis of the Indonesian state, Pancasila plays an important role in the formation of national laws and regulations. This journal examines three main aspects of the function of Pancasila in law. First, Pancasila serves as a normative framework to ensure that laws are in accordance with basic values such as justice, humanity, and unity. Second, Pancasila strengthens legal legitimacy and political consensus in the midst of modern political dynamics that are often polarized. Third, there are problems in implementing Pancasila values in law, such as inconsistencies between positive laws and people's aspirations, as well as bureaucratic constraints. In addition, the journal discusses how the values of Pancasila should be instilled and taught, how it helps strengthen constitutional democracy, as well as its relationship to economic law, human rights, environmental issues, and international law. This journal emphasizes how important it is to apply the principles of Pancasila in facing global challenges and maintaining the integrity of the nation. The research method used in this article is a qualitative approach with document analysis and literature studies on laws, court decisions, and other legal sources. The results of the study show that the application of Pancasila in law in Indonesia still faces various challenges, but it has great potential to strengthen the national legal system, especially in the aspects of social justice and constitutional democracy.